2020
DOI: 10.1093/sysbio/syaa051
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Inference of Species Trees using Diffusion Models

Abstract: Abstract We describe a new and computationally efficient Bayesian methodology for inferring species trees and demographics from unlinked binary markers. Likelihood calculations are carried out using diffusion models of allele frequency dynamics combined with novel numerical algorithms. The diffusion approach allows for analysis of datasets containing hundreds or thousands of individuals. The method, which we call Snapper, has been implemented as part of the BEAST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…A single species tree was then estimated from the UCE trees using Astral-III v. 5.7.7 [35]. Divergence times between lineages were estimated in SNAPPER v. 1.0.1 [36] using 1000 randomly selected SNPs from one individual per lineage (electronic supplementary material, table S2), with divergence of the kiwi basal split calibrated using a previous estimate of 5.96 Ma [29].…”
Section: (C) Phylogeny Constructionmentioning
confidence: 99%
“…A single species tree was then estimated from the UCE trees using Astral-III v. 5.7.7 [35]. Divergence times between lineages were estimated in SNAPPER v. 1.0.1 [36] using 1000 randomly selected SNPs from one individual per lineage (electronic supplementary material, table S2), with divergence of the kiwi basal split calibrated using a previous estimate of 5.96 Ma [29].…”
Section: (C) Phylogeny Constructionmentioning
confidence: 99%
“…However, these additional complexities in the model are met with highly efficient proposal kernels [28, 17, 25], and much like the Yule-skyline collapse model, is expected to converge quite efficiently in MCMC. Lastly, we demonstrated how the collapse model can be used for molecular sequence analysis in conjunction with StarBeast3 [25] and for SNP analysis in conjunction with SNAPPER [26] - each of which are reported to be significantly more efficient than their predecessors. We demonstrated that StarBeast3 outperforms STACEY at achieving convergence during Bayesian MCMC ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Using this method, we can run a single MCMC analysis and test a large number of hypotheses, whereas BFD* requires a path sampling run for each hypothesis under consideration, and each of these path sampling runs are at least as computationally intensive as a single MCMC run. By using SNAPPER instead of SNAPP, a further order of magnitude in performance gain is accumulated [26] [4]. For each hypothesis, the number of species, the log e marginal likelihood ML (averaged across 5 replicates), the Bayes factor BF, and the total rank are reported (with a Yule tree prior).…”
mentioning
confidence: 99%
“…Thefully-filtered dataset was used, but due to computational constraints, one random individual was selected from each of eight populations. Individuals were chosen from populations with relatively pure ancestry coefficients to avoid violating assumptions in the species tree approach, namely the effect of gene flow from other populations (see the result of sNMF analysis; Bryant et al, 2012, Stoltz et al, 2019. SNAPP was run for 30 million Markov chain Monte Carlo (MCMC) generations, with the custom program SNAPPER employed to run SNAPP at faster speed (Stoltz et al, 2019).…”
Section: Phylogenetic Tree Reconstructionmentioning
confidence: 99%
“…Individuals were chosen from populations with relatively pure ancestry coefficients to avoid violating assumptions in the species tree approach, namely the effect of gene flow from other populations (see the result of sNMF analysis; Bryant et al, 2012, Stoltz et al, 2019. SNAPP was run for 30 million Markov chain Monte Carlo (MCMC) generations, with the custom program SNAPPER employed to run SNAPP at faster speed (Stoltz et al, 2019). Two independent runs were conducted and the output trees were visualized after 10% burnin using DensiTree version 2.01 (Bouckaert 2010).…”
Section: Phylogenetic Tree Reconstructionmentioning
confidence: 99%